Physicians’ Prescription Behaviour: An Empirical Study of in the Context of Critical Diseases - BHATT, JYOTSANA (International Journal of Psychosocial Rehabilitation, 2021)
This study aims to investigate the various parameters that cause several inclinations physicians’ prescription behavior in the context of critical diseases. Patient-related factors, such as patients’ socioeconomic status and insurance coverage significantly influence physicians’ prescription behavior. Additionally, disease-related factors, such as the severity of the disease and the complexity of the treatment regimen also impact physicians’ prescription behavior. Pharmaceutical company-related factors, such as drug marketing and promotional activities, also play a crucial role in influencing physicians’ prescription behavior. Finally, physicianrelated factors, such as their experience and medical education, were found to influence prescription behavior. Overall, the study provides valuable insights into the complex nature of physicians’ prescription behavior in the context of critical diseases, highlighting the importance of various factors that influence this behavior. 247 people were surveyed to know the factors influencing prescription behaviour of physicians. These findings have important implications for healthcare policymakers, medical professionals, and pharmaceutical companies, as they provide insight into how best to address the various factors that influence prescription behavior and optimize treatment outcomes for critical diseases.